Applications for kodecytes in immunohaematology. (11th December 2017) - Henry, S.; Perry, H.; Bovin, N.
Abstract : Red cells used in immunohaematology are mostly limited to those that nature provides. Very few techniques are available for adding new functionalities to cells, without affecting their intrinsic functionality or vitality. Kode Technology is a surface modification technology that uses amphipathic function‐spacer‐lipid constructs to rapidly and harmlessly attach bioactive material to cell surfaces (creating kodecytes) and nonbiological surfaces (koded surfaces). Originally designed to attach blood group glycans onto red blood cells for quality control use, the technology has since expanded to modification of any type of cell, enveloped virus, liposome and nonbiological surfaces (including plastics, metals and glass). Today, Kode Technology and the resultant kodecytes are being used in a range of cell‐based diagnostics, as powerful research tools, and most recently as a potential immuno‐oncotherapeutic agent; soon to enter human trials. Immunohaematology applications and opportunities to use the technology in the form of kodecytes range from quality control kits, competency training panels, diagnostic reagents with synthetic rare blood group antigens or infectious disease markers. The constructs can be used for solid‐phase antibody mapping and also have potential as therapeutics, including in vivo neutralization of ABO antibodies. Together with a large range of R&D constructs, Kode Technology remains the most extensive and easy‐to‐use technology for adding bioactive material onto the surface of cells for research and diagnostics.